1991
DOI: 10.1021/bi00233a009
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of residue 45(CD3) and heme-6-propionate to the bimolecular and geminate recombination reactions of myoglobin

Abstract: Overall association and dissociation rate constants were measured at 20 degrees C for O2, CO, and alkyl isocyanide binding to position 45 (CD3) mutants of pig and sperm whale myoglobins and to sperm whale myoglobin reconstituted with protoheme IX dimethyl ester. In pig myoglobin, Lys45(CD3) was replaced with Arg, His, Ser, and Glu; in sperm whale myoglobin, Arg45(CD3) was replaced with Ser and Gly. Intramolecular rebinding of NO, O2, and methyl isocyanide to Arg45, Ser45, Glu45, and Lys45(native) pig myoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
3

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 28 publications
4
76
0
3
Order By: Relevance
“…It has been suggested that this residue acts as a gate for incoming ligands (Lambright et al, 1989;Carver et al, 1991). Aside from the His F8/por residue, the Arg CD3 residue has the largest energy contribution due to the mutation of the distal histidine (2 + 4, Table 4; 1 -+ 3, Table 5).…”
Section: Free Energy Resultsmentioning
confidence: 99%
“…It has been suggested that this residue acts as a gate for incoming ligands (Lambright et al, 1989;Carver et al, 1991). Aside from the His F8/por residue, the Arg CD3 residue has the largest energy contribution due to the mutation of the distal histidine (2 + 4, Table 4; 1 -+ 3, Table 5).…”
Section: Free Energy Resultsmentioning
confidence: 99%
“…Thus, the difference in the entropic contribution to the distal free energy barrier in eq 5 is given by (7) where S D (Mb) = k ln Ω Mb and S D (+Im) = k ln Ω +Im with Ω denoting the number of possible distal pocket states associated with the CO ligand in its initial configuration prior to geminate recombination. Thus, eq 7 leads directly to (8) We now take the number of accessible initial states for the CO ligand in Mb, Ω Mb , to be proportional to the volume of the region from which the CO ligand must return during the geminate rebinding process. Similarly, the number of possible reactant states for geminate rebinding of the CO ligand to 2-MeImFePPIX in glycerol solvent, Ω +Im , is proportional to the volume of the glycerol solvent that is displaced by the photolyzed CO ligand.…”
Section: Entropic Contribution To the Distal Barriermentioning
confidence: 99%
“…[1][2][3][4][5] The diatomic ligand binds to the heme iron from the distal side, while an amino acid residue from the protein matrix (often histidine or cysteine) binds from the other (proximal) side. The dynamics associated with ligand binding to the heme group has been studied for many years in both native and mutant proteins [3][4][5][6][7][8][9][10][11][12][13][14][15] and in heme model compounds. [16][17][18][19][20][21][22][23][24] The binding process for model compounds involves at least two steps: the diffusion of ligand through the surrounding solvent or buffer followed by the bond formation step between the diatomic ligand and the iron.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive measurements of the ligand rebinding kinetics in a wide range of human and sperm whale (SW) Mb mutants demonstrate enormous variations in both the geminate and bimolecular binding kinetics (15)(16)(17)(18)(19). Although trends can be discerned, it is often difficult to understand the effects in terms of specific interactions.…”
mentioning
confidence: 99%